A surface strengthening layer of TC4 titanium alloy based on ion implantation and ion nitriding treatment, a treatment method and application thereof

CN121046773BActive Publication Date: 2026-10-30BEIJING RES INST OF AUTOMATION FOR MACHINERY IND
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202511258432.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2025-09-04
Publication Date
2026-10-30
Estimated Expiration
2045-09-04

AI Technical Summary

Technical Problem

[0008]本发明设计开发了一种基于离子注入和离子氮化处理的TC4钛合金表面强化层,本发明的发明目的是解决了现有钛合金离子渗氮技术普遍存在的TiN脆性相不可控生成、天然氧化膜阻碍氮渗透、氮扩散受限、氮化层厚度有限及高温氮化易劣化基体性能的问题

Benefits of technology

[0027]1、本发明提供的基于离子注入和离子氮化处理的TC4钛合金表面强化层的非晶层屏蔽效应,表面非晶层阻断Ti与N的直接反应,有效抑制钛与氮直接生成TiN脆性相及TiO2氧化膜生成,同时提供大量氮原子吸附位点,使氮原子吸附富集,非晶层结构无序、表面能高,能吸附更多氮原子,显著提升表面氮浓度,为后续氮化提供丰富反应源;

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121046773B_ABST
    Figure CN121046773B_ABST
Patent Text Reader

Abstract

The application provides a processing method of a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment, and comprises the following steps: step one, vacuumizing a TC4 titanium alloy sample to be coated and then performing ion implantation; step two, introducing a mixed gas of hydrogen and argon, starting glow discharge, heating, and then keeping temperature; step three, changing the mixed gas of nitrogen, hydrogen and argon to start ion nitriding; and step four, after the ion nitriding is completed, cooling to room temperature, and then taking out the sample to obtain the TC4 titanium alloy surface strengthening layer; the application also provides a TC4 titanium alloy surface strengthening layer processed by ion implantation and ion nitriding, realizes synchronous improvement of the thickness, the compactness of the structure and the bonding force of the nitriding layer, overcomes the defects of the prior art, such as complex process, poor adaptability, unstable performance and the like, and has the advantages of obvious process simplification and performance improvement; and the application also provides an application of the TC4 titanium alloy surface strengthening layer processed by ion implantation and ion nitriding.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of titanium alloy surface hardening technology, specifically to a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment, its treatment method, and its application. Background Technology

[0002] TC4 titanium alloy (Ti-6Al-4V) is widely used in aerospace, medical devices and other fields due to its excellent specific strength, corrosion resistance and biocompatibility. However, TC4 alloy has low surface hardness and poor wear resistance, making surface nitriding an important means to improve its surface properties.

[0003] Existing ion nitriding technology improves surface hardness by injecting nitrogen ions into the surface of TC4 to form nitride phases such as TiN and Ti2N. However, due to the strong affinity between titanium and nitrogen, brittle TiN phases are easily generated during ion nitriding. Furthermore, the naturally occurring TiO2 oxide film on the TC4 surface severely hinders the effective penetration of nitrogen ions. In addition, the low diffusion rate of nitrogen in the titanium alloy matrix limits the thickness of the nitride layer (typically less than 20 μm), and the insufficient adhesion of the nitride layer makes it prone to peeling and cracking.

[0004] A patent (CN202510157418.1) discloses a method for treating the inner wall surface of a titanium alloy round tube using double-glow plasma nitriding. The method involves cleaning, drying, vacuuming, double-glow plasma nitriding, and furnace cooling. By precisely controlling parameters such as the heating rate, gas ratio, and nitriding time, the thickness and properties of the nitrided layer are accurately controlled, resulting in a TC4 round tube with a nitrided inner wall, significantly improving the hardness and wear resistance of the TC4 titanium alloy round tube's inner wall. While this patent optimizes the thickness and properties of the nitrided layer by controlling the heating rate, atmosphere ratio, and nitriding time, this method is only suitable for tubular parts with regular shapes and easily accessible inner walls to plasma. For planar structures, complex curved surfaces, and precision parts, the uniformity and operability of nitriding are severely limited. Furthermore, the process cannot suppress the formation of the brittle TiN phase at the material microstructure level, resulting in a hard but brittle coating, with persistent issues in adhesion and crack resistance.

[0005] In a patent (CN202411806333.3) for a surface strengthening method for titanium-based piston rod parts, the titanium-based piston rod parts are first subjected to tensile deformation treatment to obtain titanium-based piston rod parts with deformed microstructure; then, the titanium-based piston rod parts with deformed microstructure are subjected to isothermal recovery to obtain titanium-based piston rod parts with regulated microstructure; finally, the titanium-based piston rod parts with regulated microstructure are placed in a DC pulsed ion nitriding furnace, evacuated, and nitriding gas is introduced, and auxiliary heating and pulse power supply are turned on for heat preservation nitriding to obtain titanium-based piston rod parts with a nitrided layer on the surface. This invention uses a deformation recovery combined with ion nitriding method to effectively break and stabilize the microstructure, providing more effective channels for nitrogen atoms to diffuse into the matrix during the nitriding process, improving nitriding efficiency and nitrided layer thickness, enhancing the wear resistance of titanium-based piston rod parts, while not reducing the tensile and fatigue mechanical properties of titanium-based piston rod parts. In this patent, deformation-induced dislocations and heat treatment to regulate the microstructure effectively improve the diffusion conditions of nitrogen atoms during the nitriding process. However, this method requires significant plastic deformation of the substrate material, making it difficult to apply to complex titanium alloy structural parts or high-precision components in their finished state. Furthermore, the deformation-induced defect density and distribution are uncontrollable and the process is cumbersome, resulting in limited improvement in nitriding layer thickness and diffusion efficiency, and insufficient stability in batch processing.

[0006] In a patent (CN202411918203.9) describing a method for treating a wear-resistant coating on a titanium alloy using laser-assisted ion nitriding, the treated titanium alloy workpiece is first subjected to ion nitriding to form a nitrided layer containing a "hard shell" structure. Then, the nitrided layer is laser-remelted to destroy the "hard shell" structure. Finally, the laser-remelted titanium alloy workpiece undergoes ion nitriding again to expand the coating and form a wear-resistant coating. This method uses laser-assisted ion nitriding to prepare a wear-resistant coating on the surface of a titanium alloy workpiece. By using laser remelting to eliminate the "hard shell" structure on the surface of the nitrided layer, the thickness and quality of the wear-resistant coating are improved, and phase transformation and workpiece deformation are avoided. In this patent, the elimination of the "hard shell" structure on the surface of the nitrided layer through laser remelting improves the coating's adhesion and thickness. However, this method has a complex process flow, requiring multiple ion nitriding and laser treatments, resulting in a long manufacturing cycle and high cost. Furthermore, high-energy laser remelting can easily cause surface coarsening and thermal stress defects, leaving potential risks to the coating's microstructure stability and fatigue life.

[0007] In a patent (CN202410965792.X) describing a homogenization and gas nitriding strengthening process for titanium alloy surfaces, the surface of a titanium alloy part undergoes pretreatment. A pure titanium pre-nitriding zone with a thickness of 35-50 micrometers is prepared on the surface using plasma spraying technology. Subsequently, the titanium alloy part undergoes high-temperature gas nitriding treatment in a high-purity nitrogen atmosphere: temperature 800-1200℃, heating rate 5-15℃ / min, nitrogen flow rate 50-150ccm, and holding time 6-10 hours. This is followed by vacuum holding treatment: temperature 400-600℃, cooling rate 5-15℃ / min, and holding time 4-8 hours. After cooling to room temperature, the part is removed for post-treatment. This significantly improves the service life of the titanium alloy parts. In this patent, by pre-fabricating a pure titanium pre-zone and achieving deep nitriding in a high-temperature nitrogen environment, the surface hardness and wear resistance of the titanium alloy can be improved to a certain extent. However, this method involves nitriding temperatures as high as 800-1200℃, which easily leads to substrate grain coarsening and decreased mechanical properties. Furthermore, the preparation of the pre-layer spraying and subsequent heat treatment processes are complex, lengthy, and costly. The compositional gradient control of the nitrided layer has limited precision, making it difficult to achieve stable and reliable performance consistency. Summary of the Invention

[0008] This invention designs and develops a surface strengthening layer for TC4 titanium alloy based on ion implantation and ion nitriding. The purpose of this invention is to solve the problems commonly found in existing titanium alloy ion nitriding technologies, such as uncontrollable formation of the brittle TiN phase, natural oxide film hindering nitrogen penetration, limited nitrogen diffusion, limited nitriding layer thickness, and easy degradation of matrix properties by high-temperature nitriding.

[0009] This invention designs and develops a method for treating a surface strengthening layer of TC4 titanium alloy based on ion implantation and ion nitriding. The purpose of this invention is to construct a nanoscale amorphous layer and a high-density dislocation region on the TC4 surface by introducing ion implantation pretreatment before nitriding and by adjusting the voltage and periodicity of ion implantation dosage. By controlling the ratio and pressure of the mixed gas during the nitriding process, the nitriding reaction behavior can be regulated at the microstructure level of the material.

[0010] This invention designs and develops an application of a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment. The purpose of this invention is to solve the application problem of surface hardening of titanium alloys.

[0011] The technical solution provided by this invention is as follows:

[0012] A method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding includes the following steps:

[0013] Step 1: After cleaning the TC4 titanium alloy sample to be surface strengthened, place it in the vacuum chamber of the ion beam composite deposition system, evacuate the vacuum, and then perform ion implantation; wherein, the voltage is set to 10-50keV, the implantation dose is 1-3 cycles, and 1 cycle is 1×1017 ions / cm2.

[0014] Step 2: Purge the vacuum chamber of the ion beam composite deposition system with inert gas, turn on the first high pressure and introduce a mixture of hydrogen and argon to start glow discharge, adjust the second high pressure and then heat up, and then keep it at the temperature.

[0015] Step 3: After the heat preservation is completed, maintain the third high pressure and change the mixed gas of nitrogen, hydrogen and argon to control the vacuum degree in the vacuum chamber of the ion beam composite deposition system to 200 Pa to start ion nitriding. The nitriding time is set to 3-5 hours.

[0016] Step 4: After nitriding, cool to room temperature and remove from the furnace to obtain the TC4 titanium alloy surface strengthening layer.

[0017] Preferably, in step one, the cleaning process of the TC4 titanium alloy sample to be surface strengthened includes: ultrasonically cleaning the TC4 titanium alloy sample to be surface strengthened with acetone, alcohol and deionized water for 5-10 minutes in sequence, then taking it out and placing it in a drying oven to dry for 10 minutes, with the drying temperature set at 70°C.

[0018] Preferably, in step one, the ion implantation conditions include: the ion source target material is Zr.

[0019] Preferably, in step two, the first high voltage is 400V, and the second high voltage is 300V, which is gradually increased to 500V.

[0020] Preferably, in step two, after heating to 550-650℃, the temperature is maintained for 1-3 hours.

[0021] Preferably, in step three, the third high voltage is 500V.

[0022] Preferably, in step two, the ratio of the mixed gas of hydrogen and argon is a certain 1:1 to 1:2.

[0023] Preferably, in step three, the ratio of the mixed gas of nitrogen, hydrogen and argon is 1:2:1.

[0024] A TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding is prepared using the aforementioned treatment method for TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding. The TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding includes dislocation regions and amorphous regions sequentially formed on the TC4 titanium alloy surface after ion implantation.

[0025] An application of a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment in the surface hardening of titanium alloys, using the aforementioned TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment.

[0026] The beneficial effects of this invention are as follows:

[0027] 1. The amorphous layer shielding effect of the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment provided by this invention blocks the direct reaction between Ti and N, effectively inhibiting the direct formation of TiN brittle phase and TiO2 oxide film by titanium and nitrogen, while providing a large number of nitrogen atom adsorption sites, so that nitrogen atoms are adsorbed and enriched. The disordered structure of the amorphous layer and the high surface energy enable it to adsorb more nitrogen atoms, significantly increasing the surface nitrogen concentration and providing a rich reaction source for subsequent nitriding.

[0028] 2. The diffusion channel of the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment provided by this invention is opened: the high-density dislocation structure within 500nm reduces the diffusion barrier of nitrogen atoms, and a thick and high-quality nitriding layer can be obtained by low temperature and short time nitriding treatment, breaking through the bottleneck of nitrogen diffusion limitation in traditional processes.

[0029] 3. The TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment provided by this invention has strong adhesion: the composition of the transition zone between the nitriding layer and the substrate is continuous, the adhesion is significantly improved, and the cracking and peeling problem of traditional nitriding layers is avoided.

[0030] 4. The surface strengthening layer treatment method for TC4 titanium alloy based on ion implantation and ion nitriding provided by this invention has a wide processing window. It does not require deformation, laser remelting or high-temperature nitriding treatment. The process temperature is reduced. Through ion implantation control, the nitriding temperature is reduced to below 650℃, which avoids coarsening of the matrix grains and maintains the intrinsic mechanical properties of TC4 alloy. It takes into account both the wear resistance of the nitrided layer and the toughness of the matrix, and is suitable for surface strengthening of various geometric shapes and complex structures. Attached Figure Description

[0031] Figure 1 This is a schematic diagram of the TC4 titanium alloy surface strengthening layer structure based on ion implantation and ion nitriding treatment as described in this invention;

[0032] Figure 2This is a TEM image of the surface treated by ion implantation in Example 1 of the present invention;

[0033] Figure 3a This is a TEM image of the amorphous region treated with ion implantation according to Example 1 of the present invention;

[0034] Figure 3b This is the diffraction pattern of the amorphous region treated by ion implantation in Example 1 of the present invention;

[0035] Figure 4a This is a TEM image of a high-density dislocation treated with ion implantation according to Example 1 of the present invention;

[0036] Figure 4b This is the high-density dislocation diffraction pattern obtained by ion implantation treatment in Example 1 of the present invention;

[0037] Figure 5 This is a TEM image of the surface treated by ion implantation in Example 2 of the present invention;

[0038] Figure 6a This is a TEM image of the amorphous region treated with ion implantation in Example 2 of the present invention.

[0039] Figure 6b This is the diffraction pattern of the amorphous region treated by ion implantation in Example 2 of the present invention;

[0040] Figure 7a This is a TEM image of a high-density dislocation treated with ion implantation according to Example 2 of the present invention;

[0041] Figure 7b This is a high-density dislocation diffraction pattern obtained by ion implantation in Example 2 of the present invention. Detailed Implementation

[0042] The present invention will now be described in further detail with reference to the accompanying drawings, so that those skilled in the art can implement it based on the description.

[0043] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0044] Step 1: Material Preparation

[0045] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0046] Step 2, Ion Implantation:

[0047] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is no higher than 5 × 10⁻⁶. -3 Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 10-50 keV, and the injection dose is 1-3 cycles (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0048] Step 3, glow discharge ion nitriding:

[0049] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a 1:1-1:2 ratio to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Then, the auxiliary heat source inside the furnace is turned on to heat the parts. After the temperature reaches 550-650℃, it is held at this temperature for 1-3 hours, depending on the size of the parts. After the holding period, the high voltage is maintained at 500V, and the mixture of nitrogen, hydrogen, and argon gas is changed to a 1:2:1 ratio. The vacuum level inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 3-5 hours.

[0050] Step 4: Cooling down

[0051] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0052] like Figure 1 As shown, the present invention also provides a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment, specifically including an amorphous region 100 and a dislocation region 200, the amorphous region 100 and the dislocation region 200 forming an ion implantation region 300, and the TC4 titanium alloy surface and the ion implantation region 300 forming a TC4 titanium alloy surface strengthening layer 400.

[0053] The present invention also provides an application of a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment in the surface hardening of titanium alloys.

[0054] The present invention will be further described below with reference to specific embodiments and comparative examples.

[0055] Example 1

[0056] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0057] Step 1: Material Preparation

[0058] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0059] Step 2, Ion Implantation:

[0060] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 5 × 10⁻⁶. -3 Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 10keV, and the injection dose is 1 cycle (1 cycle is 1×10). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0061] Step 3, glow discharge ion nitriding:

[0062] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a specific ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Subsequently, the auxiliary heat source inside the furnace is turned on to raise the temperature of the auxiliary components to 550℃, and then held at this temperature for 1-3 hours. After the holding period, the high voltage is maintained at 500V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 1:2:1. The vacuum degree inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 3 hours.

[0063] Step 4: Cooling down

[0064] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0065] Example 2

[0066] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0067] Step 1: Material Preparation

[0068] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0069] Step 2, Ion Implantation:

[0070] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 5 × 10⁻⁶. -3Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 30keV, and the injection dose is 2 cycles (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0071] Step 3, glow discharge ion nitriding:

[0072] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a 1:1-1:2 ratio to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Subsequently, the auxiliary heat source inside the furnace is turned on to heat the auxiliary components. After the temperature reaches 600℃, it is held for 1-3 hours. After the holding period, the high voltage is maintained at 500V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 1:2:1. The vacuum degree inside the furnace is controlled to 200 Pa, and ion nitriding begins. The nitriding time is set to 4 hours.

[0073] Step 4: Cooling down

[0074] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0075] Example 3

[0076] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0077] Step 1: Material Preparation

[0078] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0079] Step 2, Ion Implantation:

[0080] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 5 × 10⁻⁶. -4 Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 30keV, and the injection dose is 3 cycles (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0081] Step 3, glow discharge ion nitriding:

[0082] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a specific ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Subsequently, the auxiliary heat source inside the furnace is turned on to raise the temperature of the auxiliary components to 650℃, and then held at this temperature for 1-3 hours. After the holding period, the high voltage is maintained at 500V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 1:2:1. The vacuum degree inside the furnace is controlled to 200 Pa, and ion nitriding is then initiated, with the nitriding time set to 5 hours.

[0083] Step 4: Cooling down

[0084] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0085] Example 4

[0086] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0087] Step 1: Material Preparation

[0088] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0089] Step 2, Ion Implantation:

[0090] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 5 × 10⁻⁶. -3 Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 50keV, and the injection dose is 1 cycle (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0091] Step 3, glow discharge ion nitriding:

[0092] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a specific ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Subsequently, the auxiliary heat source inside the furnace is turned on to raise the temperature of the auxiliary components to 550℃, and then held at this temperature for 1-3 hours. After the holding period, the high voltage is maintained at 500V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 1:2:1. The vacuum degree inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 4 hours.

[0093] Step 4: Cooling down

[0094] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0095] Comparative Example 1

[0096] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0097] Step 1: Material Preparation

[0098] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0099] Step 2, glow discharge ion nitriding:

[0100] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a specific ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 500V. Subsequently, the auxiliary heat source inside the furnace is turned on to raise the temperature of the auxiliary components to 550℃, and then held at this temperature for 1-3 hours. After the holding period, the high voltage is maintained at 500V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 1:2:1. The vacuum degree inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 3 hours.

[0101] Step 3: Cooling down

[0102] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0103] Comparative Example 2

[0104] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0105] Step 1: Material Preparation

[0106] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0107] Step 2, Ion Implantation:

[0108] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then evacuated to 7 × 10⁻⁶. -3 Pa, turn on the ion source, the ion source target material is Al, the voltage is set to 5keV, and the injection dose is 1.5 cycles (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0109] Step 3, glow discharge ion nitriding:

[0110] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced at a ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased to 300V. Subsequently, the auxiliary heat source inside the furnace is turned on to heat the auxiliary components. After the temperature reaches 600℃, it is held for 1-3 hours. After the holding period, the high voltage is maintained at 300V, and the ratio of nitrogen and argon gas introduced is changed to 2:1. The vacuum degree inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 2 hours.

[0111] Step 4: Cooling down

[0112] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0113] Comparative Example 3

[0114] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0115] Step 1: Material Preparation

[0116] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0117] Step 2, Ion Implantation:

[0118] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 1×10⁻⁶. -2 Pa, turn on the ion source, the ion source target material is Fe, set the voltage to 60keV, and the injection dose is 3 cycles (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0119] Step 3, glow discharge ion nitriding:

[0120] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a 1:1-1:2 ratio to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 700V. Subsequently, the auxiliary heat source inside the furnace is turned on to raise the temperature of the auxiliary components to 650℃, and then held at this temperature for 1-3 hours. After the holding period, the high voltage is maintained at 700V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 2:1:1. The vacuum degree inside the furnace is controlled to 200 Pa, and ion nitriding begins, with the nitriding time set to 6 hours.

[0121] Step 4: Cooling down

[0122] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0123] Comparative Example 4

[0124] This invention provides a method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, comprising the following steps:

[0125] Step 1: Material Preparation

[0126] Process: For TC4 parts, ultrasonically clean with acetone for 5-10 minutes, then ultrasonically clean with alcohol for 5-10 minutes, then rinse in deionized water for 5-10 minutes, take them out and place them in a drying oven to dry for 10 minutes at a temperature of 70℃.

[0127] Step 2, Ion Implantation:

[0128] Process: The TC4 component is loaded into the vacuum chamber of the ion beam composite deposition system. The vacuum level is then increased to 8 × 10⁻⁶. -3 Pa, turn on the ion source, the ion source target material is Zr, set the voltage to 80keV, and the injection dose is 1 cycle (1 cycle is 1×10⁻⁶). 17 ions / cm 2 After injection, the ion source is turned off. No gas needs to be introduced during the injection process.

[0129] Step 3, glow discharge ion nitriding:

[0130] Process: Argon gas is purged into the vacuum chamber of the ion beam composite deposition system to approximately 50 Pa. A 400V high voltage is turned on, and a mixture of hydrogen and argon gas is introduced in a specific ratio of 1:1 to 1:2 to initiate glow discharge. During this process, the high voltage is gradually increased from 300V to 800V. Subsequently, the auxiliary heat source inside the furnace is turned on to heat the auxiliary components. After the temperature reaches 550℃, it is held for 1-3 hours. After the holding period, the high voltage is maintained at 800V, and the ratio of nitrogen, hydrogen, and argon gas introduced is changed to 2:2:1. The vacuum degree inside the furnace is controlled to 200 Pa before ion nitriding begins, with the nitriding time set to 2 hours.

[0131] Step 4: Cooling down

[0132] After nitriding, the furnace is cooled to room temperature before being removed from the furnace.

[0133] Test case

[0134] In this invention, an amorphous structure and high dislocation density are formed on the surface through ion implantation, breaking the inherent limitations of uncontrollable formation of the brittle TiN phase and restricted nitrogen diffusion during the nitriding process of titanium alloys. This allows for deep penetration of the nitriding process at lower temperatures, forming a gradient transition zone between the nitrided layer and the substrate, thus improving the adhesion and wear resistance of the coating. By periodically adjusting the voltage and dosage of ion implantation, and by adjusting the ratio of the mixed gas, high pressure, and nitriding time of the nitriding ion, a surface-strengthened layer of TC4 titanium alloy can be obtained. The following performance tests were performed on Examples 1-4 and Comparative Examples 1-4:

[0135] Microhardness test: According to GB / T 4340.1-2009 "Metallic materials Vickers hardness test - Part 1: Test method", the loading and holding time is set to 10s at the 200gf force setting, and 5 points are measured for each sample.

[0136] Nitriding Depth Test: According to GB / T 11354-2005 "Determination of Nitriding Layer Depth and Metallographic Structure Inspection of Steel Parts", samples are cut from the parts after ion implantation and ion nitriding. The samples should be cut perpendicular to the nitrided layer surface. During grinding and polishing, attention should be paid to cooling to avoid overheating and edge chamfering. The surface roughness should be between Ra 0.25-0.63 μm. After etching the surface with an etchant, the surface structure is observed using an optical microscope to determine the hardening depth.

[0137] In this invention, when the ion implantation voltage is below 10 keV, the implantation effect is poor, the amorphous region is shallow, and the dislocation region is not obvious; when the voltage is above 50 keV, over-implantation occurs, and the amorphous region is shallow after being etched away, resulting in poor effect; when the implantation is less than one cycle, under-implantation occurs, making diffusion difficult and the dislocation region is not obvious; after three implantation cycles, saturation is reached, and continued implantation increases a large amount of internal stress, leading to surface cracks.

[0138] The ion implantation effect was tested on the TC4 titanium alloy surface strengthening layers from Examples 1 and 2. Figure 2 , Figure 5 As shown, the 20nm implantation region and the 500nm high-density dislocation region are clearly visible. Figure 3a , Figure 3b , Figure 6a , Figure 6b As shown, in the injection region, it exhibits an amorphous state, and the diffraction pattern displays a halo-like shape, such as... Figure 4a , Figure 4b , Figure 7a , Figure 7b As shown, below the amorphous region is a high-density dislocation region, exhibiting a polycrystalline state, with diffraction patterns in the form of circles and dots.

[0139] As shown in Table 1, the TC4 titanium alloy surface strengthening layer obtained by the present invention through ion implantation and ion nitriding treatment has a 60% increase in implantation depth and a 50% increase in surface hardness compared with traditional nitriding.

[0140] Table 1 Test Results

[0141] Example 1 950 32 Example 2 1020 35 Example 3 1100 40 Example 4 1080 38 Comparative Example 1 560 20 Comparative Example 2 620 22 Comparative Example 3 710 27 Comparative Example 4 680 25

[0142] This invention addresses both material structure regulation and diffusion kinetics mechanisms, achieving simultaneous improvements in nitrided layer thickness, microstructure density, and bonding strength. It overcomes the shortcomings of existing technologies, such as complex processes, poor adaptability, and unstable performance, and possesses significant advantages in process simplification and performance enhancement.

[0143] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for treating a surface strengthening layer on TC4 titanium alloy based on ion implantation and ion nitriding, characterized in that, Includes the following steps: Step 1: After cleaning the TC4 titanium alloy sample to be surface strengthened, place it in the vacuum chamber of the ion beam composite deposition system, evacuate the vacuum, and then perform ion implantation. In step one, the cleaning process of the TC4 titanium alloy sample to be surface strengthened includes: ultrasonically cleaning the TC4 titanium alloy sample to be surface strengthened with acetone, alcohol and deionized water for 5-10 minutes in succession, then taking it out and placing it in a drying oven to dry for 10 minutes, with the drying temperature set at 70℃. Step 2: Purge the vacuum chamber of the ion beam composite deposition system with inert gas, turn on the first high pressure and introduce a mixture of hydrogen and argon to start glow discharge, adjust the second high pressure and then heat up, and then keep it at the temperature. Step 3: After the heat preservation is completed, maintain the third high pressure and change the mixed gas of nitrogen, hydrogen and argon to control the vacuum degree in the vacuum chamber of the ion beam composite deposition system to 200 Pa to start ion nitriding. The nitriding time is set to 3-5 hours. In step three, the third high pressure is 500 V, and the ratio of the mixed gas of nitrogen, hydrogen and argon is 1:2:

1. Step 4: After nitriding, cool to room temperature and remove from the furnace to obtain the TC4 titanium alloy surface strengthening layer; In step one, the voltage is set to 10 or 50 keV, and the injection dose is for one cycle, with one cycle being 1×10⁻⁶. 17 ions / cm 2 ;or In step one, the voltage is set to 30 keV, and the injection dose is for 2 or 3 cycles, with 1 cycle being 1×10⁻⁶. 17 ions / cm 2 .

2. The method for treating the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding as described in claim 1, characterized in that, In step one, the ion implantation conditions include: the ion source target material is Zr.

3. The method for treating the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding as described in claim 2, characterized in that, In step two, the first high voltage is 400 V, and the second high voltage is 300 V, which is gradually increased to 500 V.

4. The method for treating the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding as described in claim 3, characterized in that, In step two, after heating to 550-650 ℃, the temperature is maintained for 1-3 hours.

5. The method for treating a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding as described in any one of claims 1-4, characterized in that, In step two, the ratio of the mixed gas of hydrogen and argon is 1:1 to 1:

2.

6. A surface strengthening layer for TC4 titanium alloy based on ion implantation and ion nitriding treatment, characterized in that, The TC4 titanium alloy surface strengthening layer is prepared using the treatment method of any one of claims 1-5 based on ion implantation and ion nitriding, wherein the TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding includes dislocation regions and amorphous regions sequentially formed on the TC4 titanium alloy surface after ion implantation.

7. An application of a TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding in the surface hardening of titanium alloys, characterized in that, The TC4 titanium alloy surface strengthening layer based on ion implantation and ion nitriding treatment as described in claim 6 is used.

Citation Information

Patent Citations

  • Titanium alloy surface homogenization gas nitriding strengthening process

    CN118773537A

  • A double glow plasma nitriding treatment method for the inner surface of a titanium alloy round tube

    CN119615053B

  • Surface strengthening method for titanium-based piston rod part

    CN119640201A

  • Preparation method of laser-assisted titanium alloy ion nitriding wear-resistant coating

    CN119710536A

  • Titanium alloy wear-resistant and ablation-resistant composite strengthening layer and preparation method thereof

    CN118880225A